Multivariate Macdonald Distribution and Its Properties - Daya K. Nagar; Edwin Zarrazola; Luz Estela Sánchez (Journal of Probability and Statistics)
We give multivariate generalization of Macdonald distribution and study several of its properties. We also define the multivariate Macdonald-gamma distribution and derive a number of results pertaining to it.